2010
DOI: 10.1152/japplphysiol.01058.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in-water oxygen prebreathing at different depths on decompression-induced bubble formation and platelet activation

Abstract: Effect of in-water oxygen prebreathing at different depths on decompression-induced bubble formation and platelet activation in scuba divers was evaluated. Six volunteers participated in four diving protocols, with 2 wk of recovery between dives. On dive 1, before diving, all divers breathed normally for 20 min at the surface of the sea (Air). On dive 2, before diving, all divers breathed 100% oxygen for 20 min at the surface of the sea [normobaric oxygenation (NBO)]. On dive 3, before diving, all divers breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…Nonetheless, Castagna et al found that oxygen prebreathing provides a significant reduction in decompression-induced bubble formation, regardless of the experimental conditions (Castagna et al, 2009). This is confirmed by the work of Bosco et al although hyperbaric oxygen seems more effective (Bosco et al, 2010). …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Nonetheless, Castagna et al found that oxygen prebreathing provides a significant reduction in decompression-induced bubble formation, regardless of the experimental conditions (Castagna et al, 2009). This is confirmed by the work of Bosco et al although hyperbaric oxygen seems more effective (Bosco et al, 2010). …”
Section: Discussionsupporting
confidence: 64%
“…Several practical, simple and feasible pre-dive measures have been studied such as endurance exercise (Blatteau et al, 2005; Castagna et al, 2011), pre-dive exposition to a warm environment (Blatteau et al, 2008), oral hydration (Gempp et al, 2009) or ingestion of dark chocolate (Theunissen et al, 2015). Others have tested the benefit of pre-dive oxygenation (Castagna et al, 2009; Bosco et al, 2010), or whole-body vibration (Germonpré et al, 2009). All of these studies show a positive effect with a significant decrease of post-dive VGE.…”
Section: Introductionmentioning
confidence: 99%
“…One alternative to this proposal is that a decrease in arterialization is related to an increased rate of nitrogen elimination, seen as a reduction of bubble load in the right heart. Oxygen prebreathing is used in high-altitude flights and astronaut extravehicular activity to eliminate nitrogen from the blood via an increased concentration gradient, and this principle has also been applied to SCUBA diving (2). This denucleation protocol can last between 1 and 4 h for high-altitude excursions (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was chosen not to increase the number of animals solely for that purpose. Bosco et al (2010) have shown in divers that in-water oxygen prebreathing at a depth of 6 msw or 12 msw yielded lower bubble scores than prebreathing oxygen at the surface. Their Wndings agree with the evidence for increased protection against DCS as the prebreathe oxygen pressure increases.…”
Section: Discussionmentioning
confidence: 89%
“…Three studies on humans pretreated with pure oxygen, at normobaric pressure for 30 min, 1.6 ATA for 45 min, and 1.0, 1.6, or 2.2 ATA for 20 min, are encouraging (Bosco et al 2010;Castagna et al 2009;LandolW et al 2006).…”
Section: Discussionmentioning
confidence: 97%